ChemInform Abstract: Substitution of Conventional High‐Temperature Syntheses of Inorganic Compounds by Near‐Room‐Temperature Syntheses in Ionic Liquids. Issue 6 (11th February 2014) - Groh, Matthias F.; Mueller, Ulrike; Ahmed, Ejaz; Rothenberger, Alexander; Ruck, Michael
Abstract The preparation of 16 halogenides in the Lewis‐acidic room temperature ionic liquids [bmimm]Cl·xAlCl3 (x: 1.3, 2, 4.8) demonstrates that this resource‐efficient, low‐temperature one‐pot method can successfully replace high‐temperature solid state syntheses.